Odpowiedzi

Najlepsza Odpowiedź!
2009-11-10T10:48:57+01:00
X - pierwsza liczba
x + 1 - druga liczba
x + 2 - trzecia liczba

x² + (x + 1)² + (x + 2)² - 11 = 3 x (x + 1)
x² + x² + 2 x + 1 + x² + 4 x + 4 - 11 = 3 x² + 3 x
3 x = 6

x = 2
x + 1 = 3
x + 2 = 4

Te liczby to 2, 3, 4.

Pozdro))
10 3 10
2009-11-10T14:24:54+01:00
X - pierwsza liczba
x + 1 - druga liczba
x + 2 - trzecia liczba

x² + (x + 1)² + (x + 2)² - 11 = 3 x (x + 1)
x² + x² + 2 x + 1 + x² + 4 x + 4 - 11 = 3 x² + 3 x
3 x = 6

x = 2
x + 1 = 3
x + 2 = 4

to te liczby to 2, 3, 4.
Myślę że dobrze
Pozdrawiam ;-)
3 5 3